(untitled) (LACCEI, 2024)
Petrophysical characterization employs the concept of Hydraulic Flow Units (HFU) as an essential part of the workflow. The determination of these is possible through several methods and using the Kozeny-Carman equation. However, the models to identify HFUs are used without a rigorous analysis of their functionality on all types of reservoirs. Therefore, the following work intends to propose a new discretization equation, as well as the use of the k-means algorithm to improve the results of several of these methods. In this way, the structure of the discretization models of the flow zone indicator (FZI) was analyzed, such as the Global Hydraulic Element (GHE) and Discretized Rock Type (DRT). Deficiencies were found in the approach of these methods when analyzing the construction of the new discretization equation. These methods are based on the logarithmic distribution of FZI and other factors that determine the belonging of a sample to a certain HFU. In addition, the validity of the proposed methodology was contrasted by comparing the results in the core data of the Parinas formation of the field Alvarez Oveja. Likewise, the problem of the optimal number of flow units and its importance is analyzed so as not to lack a physical meaning or lose the degree of correlation between permeability and porosity. Finally, it is recommended to use the techniques developed in the analysis of groups to solve these problems and emphasizes the dependence of the equations that relate porosity and permeability. Petrophysical characterization employs the concept of Hydraulic Flow Units (HFU) as an essential part of the workflow. The determination of these is possible through several methods and using the Kozeny-Carman equation. However, the models to identify HFUs are used without a rigorous analysis of their functionality on all types of reservoirs. Therefore, the following work intends to propose a new discretization equation, as well as the use of the k-means algorithm to improve the results of several of these methods. In this way, the structure of the discretization models of the flow zone indicator (FZI) was analyzed, such as the Global Hydraulic Element (GHE) and Discretized Rock Type (DRT). Deficiencies were found in the approach of these methods when analyzing the construction of the new discretization equation. These methods are based on the logarithmic distribution of FZI and other factors that determine the belonging of a sample to a certain HFU. In addition, the validity of the proposed methodology was contrasted by comparing the results in the core data of the Parinas formation of Campo ˜ Alvarez Oveja. Likewise, the problem of the optimal number of flow units and its importance is analyzed so as not to lack a physical meaning or lose the degree of correlation between permeability and porosity. Finally, it is recommended to use the techniques developed in the analysis of groups to solve these problems and emphasizes the dependence of the equations that relate porosity and permeability.